Genetic Diversity in Snake Gourd (Trichosanthes Cucumerina Var. Anguina L.) (Bangladesh Journal of Agricultural Research, 2022)
Multivariate analysis of fifty five genotypes of snake gourd was performed at the experimental field of Horticulture Department, Bangabandhu Sheikh Mujibur Rahman Agricultural University, Gazipur, Bangladesh from March to June, 2017 to estimate genetic diversity and choosing the potential parents for a successful hybridization program. The genotypes are grouped into six clusters according to an analysis of Principal Component Analysis (PCA) and Mahalanobis D2. The highest inter-cluster distance was noted between clusters I and VI (205.66) and the lowest between clusters II and V (38.87). The maximum intra-cluster distance was in cluster V (31.23) while the minimum was in cluster VI (15.00). Among the six clusters the IV was the most important cluster, which contains most of the desirable parent selection characters. Taking into account the magnitude of genetic divergence, cluster distance and agronomic performance, 7 parents could be selected from the clusters for the future hybridization program. Crossing among the genotypes of the selected clusters would produce high heterotic progeny.Bangladesh J. Agril. Res. 45(2): 99-111, June 2020